Photoinduced charge separation at Zn-Pd/TiO2 hybrids interface for enhanced electrochemical and photocatalytic activity. (18th August 2022) - Bamola, P; Rawat, S; Pathak, D K; Sharma, M; Dwivedi, C; Farsinezhad, S; Kumar, R; Sharma, H
Abstract: One dimensional nanostructures based hybrids have proven to be potent for photocatalytic applications. The hybrids having modified interface play a vigorous role in enrichment of photocatalytic activity by electronic interaction. Electronic interaction at interface occurs by the formation of electronic barriers (Ohmic/Schottky) that affects the transport of charge carriers and hence photocatalytic activity. The present work reports the switching of role play between Ohmic and Schottky barriers using different hybrids in order to have enhancement in photocatalytic activity. In order to form hybrids, metal nanoparticles (Pd and Zn) and bimetallic nanoparticles (ZnPd) are chosen to study the modification of interface by XPS and UPS. The analysis revealed that Pd and ZnPd crafted TiO2 nanorods (TiO2 NR) shows the formation of Schottky barrier with upward band bending at interface. Similarly, Zn crafted TiO2 NR shows the Ohmic barrier with downward band bending at interface. The band bending in hybrids is accredited to interfacial electronic interaction and charge separation at interface. The modified hybrids are studied for electrochemical analysis using cyclic voltammetry. It is analyzed that higher electrical conductivity is present in ZnPd/TiO2 NR, facilitates the transport of charge carriers. The improved charge separation at interface of ZnPd/TiO2 NR leads to enhanced photocatalytic activity in comparison to Pd/TiO2 NR and Zn/TiO2 NR.